Bulgaria : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues paper for Bulgaria highlights that the rapid credit expansion has not raised significant financial stability issues, but has been a key factor in the sharp weakening of the external current account. Although the deficit has been mostly financed by foreign direct investment (FDI) inflows, deficits of this magnitude cannot be sustained as privatization inflows will dry up with the completion of the government's privatization program. Concurrent with the surge in bank credit, the external current account has weakened, reaching a deficit of 8 1\2 percent of GDP in 2003.